Velcro Ties in Early Postoperative Pediatric Tracheostomy Care: A Systematic Review and Meta-analysis. (June 2021) - Chang, Brent A.; Gurberg, Joshua; Ware, Erin; Luu, Kimberly
Objective: To systematically review the literature to determine the difference in complications between standard twill and Velcro ties following pediatric tracheostomy. Data Sources: MEDLINE, Embase, the Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, Web of Science, and CINAHL Plus were searched up to August 2020. Review Methods: Two authors independently screened articles for eligibility. Retrospective and prospective studies were included as long as there was a direct comparison between twill and Velcro ties. Quantitative and qualitative analysis was performed. The main outcomes were skin-related complications and accidental decannulation. Results: Three studies were included in the final analysis: 1 randomized prospective trial and 2 retrospective studies. There were 238 patients total (137 twill, 101 Velcro). Combined analysis showed skin-related complications in 23% of the Velcro group and 44% of the twill group. Meta-analysis for skin-related complications showed no significant difference when comparing Velcro with standard twill ties (risk ratio, 0.53 [95% CI, 0.24-1.17]; P = .12, n = 238 participants from 3 studies, I 2 = 66%). Accidental decannulation rates were overall low and comparable between groups (1.0% of twill, 1.4% of Velcro). Conclusion: Based on limited data, skin-related complications were not statistically different between Velcro and twill ties. Accidental decannulation is rare with Velcro and standard twill ties, and both are viable options following pediatric tracheostomy.